Pentingnya Penggunaan Model Pembelajaran Project Based Learning Menggunakan Powtoon pada Pembelajaran Sejarah Siswa di MAN 2 Padang - Annisa, Reza Nurul; Hastuti, Hera (ANWARUL, 2023)
This research aims to analyze the importance of using project-based learning model using powtoon in history learning. This research uses descriptive research using the observation method. This research was conducted at MAN 2 Padang. The population in this study were all X social studies classes from class X social studies 3 which amounted to 35 people. Based on the results of research One of the learning media in history is Powtoon media. The results of this product combine powerpoint displays and comic books. The benefits of learning using powtoon are offering media options to create interesting lesson plans and produce a product that can be applied during learning.